2017
DOI: 10.2465/jmps.160718a
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report on the excess argon bearing K–feldspar from metagranite in the Brossasco–Isasca UHP Unit of Dora–Maira Massif, Italy

Abstract: The metagranite, that still preserves the igneous structure, is composed mainly of K-feldspar, plagioclase, quartz, biotite, white mica and accessory ilmenite. Quartz, K-feldspar, plagioclase and biotite preserve the original igneous shape, but are either re-equilibrated or replaced by new phases. Quartz occurs as fine-grained granoblastic aggregate, statically derived from inversion of coesite. Plagioclase is now composed of a finegrained mineral aggregate including albite, zoisite, phengite, titanite and apa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This implies that, at least in the northern DM, the D1-related P-T peak age should predate the Early Oliogocene age calculated in the southern DM (i.e. in the Brossasco-Isasca Unit; Moniè and Chopin, 1991;Gebauer et al, 1997;Itaya et al, 2017), wherein a complex tectonic stack of continental crust and ophiolitic units occurs (Henry et al, 1993;Groppo et al, 2019;Balestro et al, 2020).…”
Section: Tectonic Implications and Conclusionmentioning
confidence: 96%
“…This implies that, at least in the northern DM, the D1-related P-T peak age should predate the Early Oliogocene age calculated in the southern DM (i.e. in the Brossasco-Isasca Unit; Moniè and Chopin, 1991;Gebauer et al, 1997;Itaya et al, 2017), wherein a complex tectonic stack of continental crust and ophiolitic units occurs (Henry et al, 1993;Groppo et al, 2019;Balestro et al, 2020).…”
Section: Tectonic Implications and Conclusionmentioning
confidence: 96%
“…The high argon pressure environment created by the interaction between metasediments, peridotite and fluids would have allowed the trapping of a large amount of excess argon within phengitic micas. Recently, Itaya et al (2017) reported excess argon bearing K-feldspar from metagranite in the UHP Brossasco-Isasca Unit of DoraMaira Massif, Italy, and pointed out the possibility that the K-feldspar has trapped EAW generated by the argon release from micas during exhumation and cooling of the host lithologies. Thus, instead of total or partial resetting of the original age, the phenomenon of the trapping of the excess-argon by minerals through argon diffusion may be quite common in polymetamorphic MP-HP-UHP metamorphic rocks, depending on the closure temperature of minerals and on the presence of transient argon pressure.…”
Section: Excess-argon Wave Hypothesismentioning
confidence: 99%
“…Itaya et al (2009) and Itaya and Tsujimori (2015) later named the same phenomenon as 'Excess-Argon Wave'. Since then, the phenomenon of the trapping of 'Excess-Argon Wave' by minerals has been increasingly observed in biotite, kyanite, white mica, and K-feldspar from many types of lithologies (Itaya et al, 2005(Itaya et al, , 2009Itaya and Tsujimori, 2015;Itaya et al, 2017).…”
Section: K-ar (mentioning
confidence: 99%
See 2 more Smart Citations